2000
DOI: 10.1007/bf01280505
|View full text |Cite
|
Sign up to set email alerts
|

Novel ultrastructural observations of pea (Pisum sativum) root nodule cells by high-pressure freezing and propane-jet freezing techniques

Abstract: Summary. Pea (Pisum sativum) root nodule cells infected by the diazotroph Rhizobium leguminosarum have been well characterized by chemical fixation techniques. Propane-jet freezing and highpressure freezing were used in this study to compare rapidly frozen and chemically fixed pea root nodule cells. Cells that had been incubated in 2-(N-morpholino)ethanesulfonic acid buffer and frozen with the propane-jet freezer were better preserved than cells that had been chemically fixed or frozen with the high-pressure f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2001
2001
2004
2004

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
1
3
0
Order By: Relevance
“…Electron microscopy revealed that the plasmalemma maintains its trilaminar structure, continuity, and apposition against cell walls even at the very low water content of 0.08 g of water per g of dry mass. This is in agreement with previous freeze-fracture studies (e.g., Platt et al 1994) and TEM studies using truly anhydrous tissue processing (Browning and Gunning 1977;Opik 1980Opik , 1985Kiss et al 1990;Tiwari et al 1990;Smith 1991;Platt et al 1997;Thomson and Platt 1997;Davidson and Newcomb 2000) but different from observations following exposure to aqueous media during processing (Webster and Leopold 1977, Thomson 1979, Fincher Chabot and Leopold 1982, Yatsu 1983). Nuclear magnetic resonance and X-ray studies of orthodox seeds have also shown that membrane integrity is maintained even in the dry state and that membranes retain a lamellar configuration (Seewaldt et al 1981).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Electron microscopy revealed that the plasmalemma maintains its trilaminar structure, continuity, and apposition against cell walls even at the very low water content of 0.08 g of water per g of dry mass. This is in agreement with previous freeze-fracture studies (e.g., Platt et al 1994) and TEM studies using truly anhydrous tissue processing (Browning and Gunning 1977;Opik 1980Opik , 1985Kiss et al 1990;Tiwari et al 1990;Smith 1991;Platt et al 1997;Thomson and Platt 1997;Davidson and Newcomb 2000) but different from observations following exposure to aqueous media during processing (Webster and Leopold 1977, Thomson 1979, Fincher Chabot and Leopold 1982, Yatsu 1983). Nuclear magnetic resonance and X-ray studies of orthodox seeds have also shown that membrane integrity is maintained even in the dry state and that membranes retain a lamellar configuration (Seewaldt et al 1981).…”
Section: Discussionsupporting
confidence: 88%
“…6 d). The superior ultrastructural preservation of plant structures attained by cryotechniques is well documented (Staehelin and Chapman 1987, Craig and Staehelin 1988, Kiss et al 1990, Davidson and Newcomb 2000; for a review, see Gilkey and Staehelin 1986), which enhances the reliability of observations made on tissues prepared by such methods.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The effective cooling rate of nitrogen may be approximately doubled by the use of slush nitrogen (SN 2 ), a mixture of liquid and solid nitrogen (63 K). Melting propane was also used in this study to achieve even higher cooling rates (30,31).…”
Section: Introductionmentioning
confidence: 99%